Skip to main content

Updates ...

Visit the website 123iitjee.manishverma.site for latest posts, courses, admission & more.

For guest/sponsored article(s), please check this link.

Mathematics Problem & Solution

If the system of equations 2x – y + z =0, x- 2y + z = 0 and ax – y + 2z = 0 has infinitely many solutions and f(x) is continuous function satisfying f(x)+f(x+5) = 2, then \int\limits_0^{ - 2a} {f(x)dx} is equal to

a) 0
b) 5
c) a
d) –2a

Solution

For system of given equations to have infinitely many solutions, we must have

\left| {\begin{array}{ccccccccccccccc}<br />2&{ - 1}&1\\<br />1&{ - 2}&1\\<br />a&{ - 1}&2<br />\end{array}} \right| = 0

or, 2x(-3) + 2-a + (-1+2a) = 0

or, a = 5

Now,

\int\limits_0^{ - 2a} {f(x)d} x

 = \int\limits_0^{ - 10} {f(x)d} x

 = \int\limits_0^{ - 5} {f(x)d} x + \int\limits_{ - 5}^{ - 10} {f(x)d} x

 = \int\limits_0^{ - 5} {f(x)d} x + \int\limits_0^{ - 5} {f(u - 5)du} ,{\rm{ putting x + 5 = u for the second integral}}

 = \int\limits_0^{ - 5} {f(x)d} x + \int\limits_0^{ - 5} {2 - f(u)du} ,

                             \left[ \begin{array}{l}<br />{\rm{Given, f(x)  +  f(x + 5)  = 2}}\\<br />{\rm{Replacing x by u  -  5, }}f(u - 5) + f(u) = 2<br />\end{array} \right]

 = \int\limits_0^{ - 5} {f(x)d} x + \int\limits_0^{ - 5} {2 - f(x)dx} ,{\rm{ Replacing u by x in the second integral}}

= –10 = -2a

Hence, (d).

Popular posts from this blog

$f(x)=x^6+2x^4+x^3+2x+3 $

$\mathop {\lim }\limits_{x \to 1} \frac{{{x^n}f(1) - f(x)}}{{x - 1}} = 44$

$n=?$

Let $f(x)=x^6+2x^4+x^3+2x+3,x \in R $. Then the natural number n for which $\mathop {\lim }\limits_{x \to 1} \frac{{{x^n}f(1) - f(x)}}{{x - 1}} = 44$ is _ _ _ _ . Solution Since the limit has $\left[ {\frac{0}{0}} \right]$ form, L.H. Rule is applicable. Thus, $\mathop {\lim }\limits_{x \to 1} n{x^{n - 1}}f(1) - f'(x) = 44$ $\therefore nf(1) - f'(1) = 44$ $\therefore n.9 - ({6.1^5} + {8.1^3} + {3.1^2} + 2.1) = 44$ $ \Rightarrow 9n - 19 = 44$ $\Rightarrow n=7$